1994
DOI: 10.1130/spe291-p171
|View full text |Cite
|
Sign up to set email alerts
|

An integrated geophysical study of the Estancia Basin, central New Mexico

Abstract: This study focuses on the interpretation of seismic reflection lines, gravity, and well data in the EstanciaBasin, which is located along the eastern margin of the Rio Grande rift in central New Mexico. Major new data introduced are seven seismic reflection lines provided by the Mobil Exploration and Production Company. The basin began to form during Late Mississippian and Early Pennsylvanian uplift of the Ancestral Rocky Mountains. Laramide-age thrusting and folding occurred west of the basin and may have cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The extensive reflection data in the Albuquerque basin reported by Russell and Snelson (1994) showed that this basin is divided into two sub-basins with opposite fault polarities. East of the Albuquerque basin, the Estancia basin is covered by a grid of seismic lines, summarized in Barrow and Keller (1994). These data show that there are many reflectors within the basement and that this basin is a pull-apart structure related to the Ancestral Rocky Mountains (Pennsylvanian).…”
Section: Reflection Profilesmentioning
confidence: 97%
“…The extensive reflection data in the Albuquerque basin reported by Russell and Snelson (1994) showed that this basin is divided into two sub-basins with opposite fault polarities. East of the Albuquerque basin, the Estancia basin is covered by a grid of seismic lines, summarized in Barrow and Keller (1994). These data show that there are many reflectors within the basement and that this basin is a pull-apart structure related to the Ancestral Rocky Mountains (Pennsylvanian).…”
Section: Reflection Profilesmentioning
confidence: 97%
“…The Estanica Basin lies between the middle Rio Grande and Pecos valleys and is a large structural basin which is part of the Rio Grande Rift system (Barrow and Keller 1994). The basin likely closed and began filling with sediment in the late Tertiary or early Pleistocene (Allen and Anderson 2000).…”
Section: Changing Environments and Fluctuating Lake Levelsmentioning
confidence: 99%
“…1) is an asymmetric structural depression that has existed as a depositional basin from Morrowan (Early Pennsylvanian) through Recent time. The basin has undergone three major stages of tectonic deformation (Chapin, 1971;Chapin and Cather, 1981;Chapin, 1991, 1994;Barrow and Keller, 1994;Broadhead, 1994): 1) late Paleozoic (Pennsylvanian-Early Permian) deformation associated with formation of the ancestral Rocky Mountains; 2) Laramide deformation from the Late Cretaceous through the Eocene; and 3) multiphase extensional deformation, beginning in the Oligocene, associated with formation of the Rio Grande rift.…”
Section: Structurementioning
confidence: 99%
“…Seismic reflection profiles were indispensable to the construction of the subsurface structure-contour maps. Barrow and Keller (1994) provided an integrated picture of gravity, magnetic, and reflection seismic data within the basin. Of particular importance were the seismic reflection profiles provided to Barrow and Keller by Mobil Exploration and Production.…”
Section: Structurementioning
confidence: 99%